Health care workers and AIDS: a differential study of beliefs and affects associated with accidental exposure to blood Profissionais de saúde e AIDS: um estudo diferencial sobre crenças e afetos associados à experiência de exposição acidental a material biológico potencialmente contaminado - Maria Rosa Rodrigues Rissi; Alcyone Artioli Machado; Marco Antonio de Castro Figueiredo (Escola Nacional de Saúde Pública, Fundação Oswaldo Cruz, 2005)
This study aimed to analyze affective and cognitive determinants of the professional work of individuals caring for patients with HIV/AIDS, in view of the risk and/or experience of accidental exposure to blood. We drew on the theoretical-methodological references of Fishbein & Ajzen and Maslow's theory. Fifty health care workers were evaluated using an attitudes questionnaire and a needs and motivations instrument. The research verified differences between answers by health care workers who had never suffered accidents and those who had already experienced accidental exposure to blood. Health care workers did their work activities motivated by the need for self-fulfillment and valued their own performance when they were able to meet the patients' emotional needs. Among health professionals who had never experienced accidental exposure to blood, the predominant beliefs was that patients feel remorse over having expose themselves to HIV. Accidental exposure to blood raises difficulties in personal life. Technical aspects are also associated with the possibility of accidental exposure to blood. O objetivo deste estudo foi analisar determinantes afetivos e cognitivos que influenciam o trabalho de profissionais que cuidam de pessoas vivendo com o HIV/ AIDS, frente ao risco ou experiência de exposição acidental a material biológico potencialmente contaminado (MBPC). Utilizou-se o referencial teórico metodológico de Fishbein-Ajzen e a teoria de Maslow, que propõe a hierarquia das necessidades humanas. Cinqüenta profissionais de saúde foram avaliados por meio de escalas de atitudes, e de um instrumento de avaliação de necessidades e motivações. Verificou-se a diferença entre as respostas de profissionais que nunca sofreram acidente e aqueles que já passaram pela experiência de acidente ocupacional. Os resultados indicam que os profissionais exercem suas atividades motivados pela necessidade de auto-realização e valorizam sua performance quando podem atender as necessidades emocionais dos pacientes. Para os profissionais que não se acidentaram predominam crenças de que os pacientes se arrependem da exposição ao HIV. O episódio de acidente acarreta dificuldades à vida pessoal e profissional do trabalhador acidentado. Aspectos técnicos também aparecem associados à possibilidade de ocorrência de acidentes.